2020
DOI: 10.12961/aprl.2020.23.03.06
|View full text |Cite
|
Sign up to set email alerts
|

Estrés postraumático en trabajadores de salud expuestos a COVID-19

Abstract: Sr. Director recientemente se publicó el estudio titulado “Revisión sistemática sobre la reducción de efectos emocionales negativos en trabajadores del área de emergencias y catástrofes mediante técnicas de catarsis” que tiene como objetivo evaluar la heterogeneidad existente en la aplicación de técnicas de catarsis en los trabajadores que atienden situaciones de emergencia y el trastorno de estrés postraumático1 hemos decido comentar sus conceptos en el contexto actual de la pandemia COVID-19. El trastorno de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 3 publications
0
2
0
6
Order By: Relevance
“…PTSD is a chronic mental illness that generally develops after being exposed to severe trauma, intrusive memories, distressing dreams, and a negative mood. It is estimated that approximately 6% of people exposed to psychological trauma go on to develop PTSD ( 57 ); according to this data and other references, it is considered that severe stages of anxiety, depression, or stress are risk factors for having PTSD and severe PTSD. These results are related to gender differences since it has been shown that women with some susceptibilities have a higher risk of being affected by PTSD ( 77 ).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…PTSD is a chronic mental illness that generally develops after being exposed to severe trauma, intrusive memories, distressing dreams, and a negative mood. It is estimated that approximately 6% of people exposed to psychological trauma go on to develop PTSD ( 57 ); according to this data and other references, it is considered that severe stages of anxiety, depression, or stress are risk factors for having PTSD and severe PTSD. These results are related to gender differences since it has been shown that women with some susceptibilities have a higher risk of being affected by PTSD ( 77 ).…”
Section: Discussionmentioning
confidence: 96%
“…It was determined that a minimum sample size of 3,204 was necessary to achieve a minimum percentage difference of 2.5% (49.0% vs. 51.5%), a statistical power of 80%, and a confidence level of 95% (data not shown). The sample size was calculated using power analysis ( 56 ) and based on a previous study in Peru that assessed PTSD after a natural phenomenon ( 57 ). Residents of the countries in question were included who reported that they remained in those territories during the time of the pandemic and who agreed to participate in the research.…”
Section: Methodsmentioning
confidence: 99%
“…Por lo tanto, precisar cuantitativamente el nivel de MDA permitiría proponer un tratamiento efectivo ante los daños ocasionados por el estrés (13) .…”
Section: Introductionunclassified
“…En este sentido, durante estos dos últimos años se ha producido un aumento exponencial y sostenido de visitas, desde unas 200 en marzo de 2020 a unas 3.500 en junio de 2022. Los cuatro artículos cuyos resúmenes han sido más leídos con diferencia, entre 3.081 y 9.894 visitas al resumen y también el artículo completo (entre 1.845 y 8.102 visitas, datos de 28 de junio de 2022) abordan un tema relacionado con la pandemia (6)(7)(8)(9) . Ello muestra que la revista no solo publica conocimiento actualizado sino también atiende las necesidades de los lectores.…”
unclassified